Passive sampling of pesticides and polychlorinated biphenyls along the Quequén Grande River watershed, Argentina. (9th January 2019) - Silva‐Barni, María Florencia; Smedes, Foppe; Fillmann, Gilberto; Miglioranza, Karina Silvia Beatriz
Abstract: Water monitoring is of great importance, especially for water bodies in agricultural or industrial areas. Grab sampling is a widely used technique for aquatic monitoring but represents only a snapshot of the contaminant levels at a specific point in time. Passive sampling, on the other hand, is an integrative technique that provides an average concentration of contaminants representative of its deployment period. Thus, the current contamination by organochlorine pesticides, polychlorinated biphenyls (PCBs), and some currently used pesticides was assessed along the Quequén Grande River watershed (Argentina) using the integrative silicone rubber passive sampling technique in a year‐long study. Silicone rubber samplers were deployed at 6 sampling sites selected according to different land uses (agricultural–livestock production, agricultural and urban activities) during 3 periods in 2014 and 2015. The organochlorine pesticides were dominated by endosulfan (sum of α‐, β‐endosulfan, endosulfan sulfate = 0.15–23.4 ng/L). The highest endosulfan levels were registered during the pesticide application period (December–March), exceeding the international water quality guidelines for protecting freshwater biota (3 ng/L). Compared with previous reports, no reductions in endosulfan levels were observed at the Quequén Grande River watershed. These results would suggest the illegal use of remaining stocks because water sampling was carried out after endosulfan was banned in Argentina. Chlorpyrifos was the second major pesticide found in water (0.02–4.3 ng/L), associated with its widespread usage on soybean crops. A reduction in levels of legacy pesticides (heptachlors, DDTs, dieldrin, and chlordanes) was evident compared with previous reports from 2007. Levels of PCBs were very low, indicating that probably only minor diffuse sources were still available along the Quequén Grande River watershed. Environ Toxicol Chem 2019;38:340–349. © 2018 SETAC